POTATO PRAWN CHEESE BALL : Inovasi Produk Berbasis Kentang Dan Udang Sebagai ide Bisnis Kuliner Kekinian: Inovasi produk, kuliner kekinian, kentang, udang, peluang usaha, ekonomi kreatif. - Aftesia Labira Lauli; Sinta Bela Farah Kirani; Karyadi Hidayat (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The culinary sector in Indonesia is experiencing rapid growth in line with the increasing public demand for practical, delicious, and aesthetically pleasing food. Innovation in food product development is a crucial factor for businesses to compete in an increasingly competitive and changing market. Potato Prawn Cheese Balls are an example of a culinary product innovation that combines potato, shrimp, and cheese, offering a distinctive flavor while meeting the tastes of modern consumers. This combination of ingredients not only provides an appealing texture crispy on the outside and soft and savory on the inside but also enhances the nutritional value and appeal of the product.This product research and development was conducted to assess the potential of Potato Prawn Cheese Balls as a culinary business idea that aligns with consumer trends, particularly among the younger generation, who tend to choose innovative, practical, and attractive foods on social media. This study was conducted through a literature review on product innovation, consumer preferences, culinary trends, and an analysis of the added value of local ingredients. The study findings indicate that Potato Prawn Cheese Balls have significant potential for development as a modern culinary business due to their product characteristics that meet market demand, are easy to produce, flexible in presentation, and have the potential to create high economic value.This innovation is expected to be an alternative business opportunity that is relevant and promising in the creative economy era. Keywords: product innovation, contemporary culinary, potatoes, shrimp, business opportunities, creative economy. Pertumbuhan sektor kuliner di Indonesia mengalami perkembangan yang pesat seiring dengan meningkatnya kebutuhan masyarakat akan makanan yang praktis, lezat, dan estetis. Inovasi dalam pengembangan produk makanan menjadi faktor penting bagi pelaku usaha untuk bersaing di pasar yang semakin kompetitif dan berubah-ubah. Potato Prawn Cheese Ball adalah contoh inovasi produk kuliner yang menggabungkan kentang, udang, dan keju, menawarkan rasa yang khas sambil memenuhi selera konsumen modern. Kombinasi bahan ini tidak hanya memberikan tekstur yang menarik renyah di luar dan lembut serta gurih di dalam tetapi juga meningkatkan nilai gizi dan daya tarik produk tersebut.Penelitian atau pengembangan produk ini dilaksanakan untuk menilai potensi Potato Prawn Cheese Ball sebagai ide bisnis kuliner yang sesuai dengan tren konsumsi masyarakat, terutama di kalangan generasi muda yang cenderung memilih makanan yang inovatif, praktis, dan menarik di media sosial. Kajian ini dilakukan melalui tinjauan literatur mengenai inovasi produk, preferensi konsumen, tren kuliner, dan analisis nilai tambah dari bahan-bahan lokal. Temuan kajian menunjukkan bahwa Potato Prawn Cheese Ball memiliki peluang yang signifikan untuk dikembangkan sebagai usaha kuliner modern karena karakteristik produk yang sesuai dengan permintaan pasar, mudah untuk diproduksi, fleksibel dalam penyajian, serta memiliki potensi untuk menciptakan nilai ekonomi yang tinggi. Inovasi ini diharapkan bisa menjadi alternatif peluang bisnis yang relevan dan menjanjikan di era ekonomi kreatif. Kata Kunci: Inovasi produk, kuliner kekinian, kentang, udang, peluang usaha, ekonomi kreatif.